Improving agricultural value chain coordination and gender inclusiveness in PNG - Kosec, Katrina; Schmidt, Emily; Carrillo, Lucia; Fang, Peixun; Ivekolia, Mark; Ovah, Raywin (International Food Policy Research Institute, 2022)
The welfare of Papua New Guinea’s (PNG’s) population depends on domestic agriculture productivity and stability. As of 2019, value-added from the agriculture, forestry, and fishing sectors totaled approximately 17 percent of GDP. However, when considering the downstream value chain activities directly related to the agriculture sector (e.g., agriculture processing, domestic food trade and transportation, and domestic food commodity sales), the larger agri-food system in PNG contributes over 25 percent to the country’s overall GDP (Pradesha and Dorosh, 2022). Maximizing efficiency throughout the entire agri-food value chain is critical to fostering greater economic growth and poverty reduction within the country. Growing a globally competitive agriculture sector also demands investments and capacity strengthening in mid-stream value chain operations such as product aggregation, transport logistics, packaging and processing, and handling. It is important that these investments also promote inclusive development that benefits both men and women value chain actors. Previous research suggests that where women are economically empowered and have access to decent jobs in lucrative nodes (i.e., activities) of value chains, households have higher incomes and are less likely to be poor (FAO, 2011). In PNG, despite women’s greater share of employment in agriculture (60 and 52 percent of women and men work in agriculture, respectively), women participate less in higher-value agricultural production and trade activities (Chang et al., 2016; Omot, Chambers, and Spriggs, 2013; World Bank, 2022).